2021
DOI: 10.1158/0008-5472.can-21-1175
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Carbon-Bound Exogenous Compounds in Patients with Lung Cancer and Association with Disease Pathophysiology

Abstract: Asymptomatic anthracosis is the accumulation of black carbon particles in adult human lungs. It is a common occurrence, but the pathophysiologic significance of anthracosis is debatable. Using in situ high mass resolution matrix-assisted laser desorption/ionization (MALDI) fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometry imaging analysis, we discovered noxious carbon-bound exogenous compounds, such as polycyclic aromatic hydrocarbons (PAH), tobacco-specific nitrosamines, or aromatic amines,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In order to determine the prognostic power for each metabolite, the individual patient metabolite abundances were used to split the cohort into good and poor survivor groups by the application of intensity cutoffs, which were optimized to the clinical endpoint. Cutoff-optimized survival analyses were performed as previously described [ 23 , 24 ] using a Kaplan–Meier Fitter and log-rank test. Cutoff-optimized in this context means that the threshold for low and high abundance of a compound was chosen such that the p -value in the resulting Kaplan–Meier curve is minimal.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the prognostic power for each metabolite, the individual patient metabolite abundances were used to split the cohort into good and poor survivor groups by the application of intensity cutoffs, which were optimized to the clinical endpoint. Cutoff-optimized survival analyses were performed as previously described [ 23 , 24 ] using a Kaplan–Meier Fitter and log-rank test. Cutoff-optimized in this context means that the threshold for low and high abundance of a compound was chosen such that the p -value in the resulting Kaplan–Meier curve is minimal.…”
Section: Methodsmentioning
confidence: 99%
“…The entire workflow is applied to the same tissue section, allowing for the automatic integration of morphological and spatial metabolomics data for thousands of molecules. We established this method and have successfully applied it in previous works [27,[44][45][46]. Supplementary Figure S1 displays representative immunofluorescence sections used during this process.…”
Section: Immunophenotype-guided Msi Analysis Data Processing and Path...mentioning
confidence: 99%
“…12 Our previous study demonstrated that carbon-bound PAHs, tobacco-specific nitrosamines, aromatic amines, and organohalogens are strongly associated with patient outcomes, tumor development, and the tumor microenvironment in lung squamous cell carcinoma (LUSC). 13 However, the roles of these exogenous compounds in lung adenocarcinoma (LUAD) remain unclear. LUAD is the most common lung cancer type, accounting for 30% of all lung cancer cases and approximately 40% of all nonsmall cell lung cancer (NSCLC) occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al found that the polycyclic aromatic hydrocarbon (PAH) accumulation in pulmonary carbon particles increases with age, which could potentially increase the risk of lung cancer development . Our previous study demonstrated that carbon-bound PAHs, tobacco-specific nitrosamines, aromatic amines, and organohalogens are strongly associated with patient outcomes, tumor development, and the tumor microenvironment in lung squamous cell carcinoma (LUSC) . However, the roles of these exogenous compounds in lung adenocarcinoma (LUAD) remain unclear.…”
Section: Introductionmentioning
confidence: 99%